If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x-3=9x+8
We move all terms to the left:
9x-3-(9x+8)=0
We get rid of parentheses
9x-9x-8-3=0
We add all the numbers together, and all the variables
-11!=0
There is no solution for this equation
| -6x-40=17 | | 1=-3x-11+5x-8 | | 6a+-19=30a | | 15z-12z-2z=2 | | x/4=8-x | | 1x-14+(-3)=25 | | 31(w+465)=806 | | 8p+3p+4p+3p+2p=20 | | 6(2 | | 23-7h=65 | | 160+3=195=2=x | | 2x+1+x+6=3x-4 | | -7p-10=53 | | 12c-11c=7 | | 5/3n-1=3/2n+4 | | (5x+15)=(4x-6) | | −5x+2=27 | | -2/3y+9=5 | | 4x+44=2x+20 | | 3y+5=y=11 | | (5x+22)+(3x+24)+x=180 | | v+4=78 | | -5-6x=6x-41 | | -14=w/7-19 | | 4x-44=2x-20 | | 13x-12=4x-5 | | 10+3p=46 | | 4h=–5+5h | | 8=q+15* | | 1.7(2+5b)=40b-6 | | ¾=3/8x-3/2 | | x–9=-3 |